STUDI IMPLEMENTASI TRADISIONALISASI DAN MODERNISASI PENDIDIKAN DI PONDOK PESANTREN - Evita Yuliatul Wahidah (MUADDIB Jurnal Kependidikan dan Keislaman, 2015)
Changes or modernization of islamic education in Indonesia which related to the idea of islamic modernization affect the science dynamics on educational environments, including Pesantren. The idea of Islamic modernization finds its momentum since in the beginning of 20 century AD, on the educational field is realized with the establishment of modern educational institution. Boarding School (Pondok Pesantren) as an educational institution could not avoid modernization which penetrated and influenced all places and regions. A concrete manifestation of this modernization in the educational management at boarding school is including: management of formal education done in kindergarten (TK), Madrasah Ibtidaiyah (MI), Mdrasah Tsanawiyah (MTs), and Madrasah Aliyah (MA) and the management of education and teaching outside the formal school hours which is undertaken by the parenting teacher with some supporting factors. From the study it was found that the boarding school had successfully showed the strength of Islamic educational institution despite the implementation of modern learning pattern and system.Boarding school was still actively educating people with its role and function as an alternative instituion, that were: a commitment on Tafaqquh Fiddin, a whole time education (full day school), integrated education (integrative), a whole education (affective, cognitive, psychomotor), a free diversity, independent, and responsible, as well as a small society